Sex differences in antidepressant efficacy. (January 2019) - LeGates, Tara; Kvarta, Mark; Thompson, Scott
Abstract Sex differences have been observed across many psychiatric diseases, especially mood disorders. For major depression, the most prevalent psychiatric disorder, females show a roughly two-fold greater risk as compared to males. Depression is sexually dimorphic with males and females exhibiting differences in clinical presentation, course, and response to antidepressant treatment. In this review, we first discuss sex differences observed in depressed patients, as well as animal models that reveal potential underlying mechanisms. We then discuss antidepressant treatments including their proposed mechanism of action and sex differences observed in treatment response. We include possible mechanisms underlying these sex differences with particular focus on synaptic transmission.